Senna Makki and the COVID-19 pandemic: a reflection from Pakistan - Kumar, Sahil; Naeem, Ramsha; Radhawi, Anum Syed Tauqir; Mahmood, Syed Uzair; Batool, Zehra; Naqi, Syed Roshaan Ahmed (International Journal Of Community Medicine And Public Health, 2020)
The outbreak of the novel coronavirus (SARS-CoV-2) since December 2019 has created an unprecedented state. As it is a new variant of a virus treatment options are not only limited but require painstaking trials to confirm their effectiveness. Due to the lack of awareness in many developing countries people have started using herbal medications, used for various other diseases, to combat COVID-19. Misleading information on social media regarding “Senna Makki” has gone viral in Pakistan. However, consumption of Senna Makki is not advised as a treatment option for COVID-19 due to its many harmful associated side-effects. Although its use in other diseases is evident, trials to confirm its effectiveness against COVID-19 need to be prioritized as the public has started consuming Senna Makki in high doses and without monitored prescription.